Hollow Pike where witchcraft never sleeps - Dawson, Juno 1981- (Indigo, 2012)
Lis London is hoping for a fresh start when she arrives in the sleepy village of Hollow Pike - but nothing here is as it seems ... Lis has a recurring nightmare where someone is trying to kill her. A ritual murder in the woods - just like her dream - makes Lis think she might be next to die. A killer stalks the night. And the birds ... see ... everything ... Hollow Pike - where witchcraft never sleeps